A Proposed Communication Network Concept for Emergency Phases in Banda Aceh - Zahrul Maizi; Zuhar Musliyana (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Communication problems during emergency situations caused by diverse natural phenomenon, especially earthquake, often occurred in Banda Aceh. Thus, this paper purposes to propose a sophisticated network infrastructure for an effective communication in time of emergency phase. Considering the needs for better communication that can lead to efficient responses in disaster emergency, we try to present a concept of Wireless Mesh Network (WMN) as one of the most effective communication network solutions for today that can perform well in crisis phases. The proposed concept in this paper refers to some existing literatures to develop a reliable communication network that will perform better, especially in time of emergency and other chaotic situations caused by natural phenomenon. This paper draws attention to the existence of a sophisticated network infrastructure in Banda Aceh as it is one of the most prone areas to disasters in Aceh, especially earthquake and tsunami. This paper also urges all stakeholders, like local government, communication providers and other related parties to take this communication solution into consideration thus the communication problems during an emergency phase can be minimized.Keywords: emergency phase, communication network, WMN